1999
DOI: 10.1161/01.atv.19.7.1669
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Connexin43 and Desmin Defines Two Subpopulations of Medial Smooth Muscle Cells in the Human Internal Mammary Artery

Abstract: Abstract-Upregulation of connexin43-gap junctions is associated with transition of contractile vascular smooth muscle cells (SMCs) to the synthetic state. To determine whether phenotypically distinct subpopulations of medial SMCs differentially express connexin43, we investigated the human distal internal mammary artery, a structurally heterogeneous vessel with features ranging from elastic to elastomuscular to muscular. Immunoconfocal microscopy combined with quantitative analysis and complemented by in situ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
33
2

Year Published

2000
2000
2007
2007

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 56 publications
2
33
2
Order By: Relevance
“…The finding of 2 SMC types that modestly differ in expression of differentiation markers is noteworthy given a recent description of 2 SMC phenotypes evident in the media of the human internal thoracic artery differing in expression of desmin and connexin43, but not by the stainable presence of 5 other SMC-associated proteins including SM MHC. 13 Although such subtle distinctions in expression of SMC differentiation markers could be caused by variations in the local microenvironment, the present results indicate that they can also reflect intrinsic differences between SMC subtypes.…”
Section: Discussionmentioning
confidence: 54%
See 2 more Smart Citations
“…The finding of 2 SMC types that modestly differ in expression of differentiation markers is noteworthy given a recent description of 2 SMC phenotypes evident in the media of the human internal thoracic artery differing in expression of desmin and connexin43, but not by the stainable presence of 5 other SMC-associated proteins including SM MHC. 13 Although such subtle distinctions in expression of SMC differentiation markers could be caused by variations in the local microenvironment, the present results indicate that they can also reflect intrinsic differences between SMC subtypes.…”
Section: Discussionmentioning
confidence: 54%
“…[15][16][17] Unfortunately, the extent to which the concepts arising from animal studies can be reliably extrapolated to human arterial behavior is limited. Although there is a small amount of in situ evidence for medial SMC diversity in humans, 11,13 there has been little success at isolating stable and clearly distinguishable subpopulations of SMCs from adult human arteries. The difficulty in cloning human SMCs is well recognized and illustrated by a report of cloning that yielded anchorage-independent cell colonies, implying a loss of physiological growth control as a precursor to cloning.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…14 Because macrophages and other leukocytes account for only a small percentage (Յ1%) of the total cell number in the neointima of balloon-injured rat carotid arteries, 15 the authors proposed that Cx43 communication enabled SMCs to coordinate synthesis of extracellular matrix components, to maintain the functional integrity of the media, and/or to regulate repair and neointimal formation in injured vessels. 16 Enhanced Cx43 expression in vascular SMCs and neointimal macrophages was reported later in restenotic lesions of injured rabbits. 17,18 Indeed, in vitro studies confirmed the presence of Cx43 in stimulated primary macrophages or in macrophage cell lines.…”
Section: Clinical Perspective P 2843mentioning
confidence: 92%
“…17 The variations between SMCs within a particular vessel, both with respect to marker gene expression and functional and morphological characteristics, suggest that there may be a genetic basis for SMC diversity. After all, such SMCs share similar embryological origins and experience comparable local conditions.…”
mentioning
confidence: 99%